International Legal Standards Pertaining to Sexual Violence Against Displaced Women in Times of Armed Conflict with Special Reference to the Emerged Jurisprudence at the ICTY and the ICTR - Seneviratne, Wasantha (Sri Lanka Journal of International Law, 2008)
Displaced women are vulnerable to all forms of violence at every stage of their flight, not only when fleeing a battlefield but also on arrival at a refugee camp. In situations of armed conflict, acts of sexual violence against displaced women are more common and widespread. This article focuses on the problem of sexual violence against displaced women and examines the strengths and weaknesses of the international legal standards that have been formulated on the issue. It further evaluates the jurisprudence emerged at the ICTY and ICTR on this problem and the future work of the ICC.
Keywords: Sexual violence against displaced women; Armed Conflict; Emerged Jurisprudence; ICTY; ICTR